PHYSIOLOGICAL RESPONSE OF WHEAT (Triticum aesitivum L.) VARIETIES AS INFLUENCED BY SALINITY STRESS - J. Din; S.U. Khan; I. Ali (Journal of Animal and Plant Sciences, 2008)
Response of seven wheat (Triticum aesitivum L.) varieties; Lu-26, Inqilab-91, Bakhtawar, Parwaz-93, Pak-81, Pasban-90 and Potohar-1 was determined under NaCl salinity in glasshouse. The plans were exposed to 100 mol m-3 NaCl and its effect on physiological parameters relating to salinity tolerance like; relative growth rate, chlorophyll contents, proline accumulation, Na+, K+ uptake and their fluxes was recorded. The relative salinity tolerance of the wheat varieties was determined on the basis of their survival percentage in 400 mol m-3 NaCl. The survival percentage was greater of LU-26 (85%) followed by Punjab-85 (65%) and Inqalab-91 (55%). The survival of other varieties was between 25-40 %. K: Na and, Chlorophyll contents were greater in Lu-26, followed by Punjab-85 and Inqalab-91. The same varieties showed greater fluxes of K+ and lesser of Na+. Based on the survival percentage and physiological data the wheat variety Lu-26, performed best followed by Inqalab-91 and Punjab-85 were also found better under saline conditions. Bakhtawar, Potohar, Parwaz, Pasban, and Pak-81 were relatively salt sensitive and showed less survival, relative growth rate and higher uptake of sodium under NaCl salinity. Physiological parameters like low fluxes of Na+ and high of K+, high shoot K:Na and chlorophyll contents were found to be useful parameters related to salinity tolerance of wheat.
Keywords: Salinity; wheat; sodium and potassium uptake; K: Na; chlorophyll; proline